1997
DOI: 10.1021/om960914n
|View full text |Cite
|
Sign up to set email alerts
|

Flash Vacuum Thermolysis:  First Gas-Phase Generation of Unhindered Silylidenephosphanes and Characterization by Photoelectron Spectroscopy

Abstract: The flash vacuum thermolysis of cyclodisilaphosphanes, cyclotrisilaphosphanes, and a phosphasilacyclobutane, potential precursors of unhindered silylidenephosphanes (R2SiPR‘), has been investigated by NMR as well as by coupling with HRMS and, particularly, photoelectron spectroscopy. This last technique led us to characterize for the first time, in the gas phase, two very reactive species of this series, the P-tert-butyl- and P-phenyl(dimethylsilylidene)phosphanes (Me2SiP-t-Bu and Me2SiPPh). The first ioniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…[24,35,40] The calculated energies of the two first ionic states, associated with the ejection of an electron from the heteroatom lone pair and from the π SiϭX bond, reflect the experimentally observed ionizations fairly well for all the heterosilenes investigated. This experimental and theoretical data set enables the differences in electronic structure between related SiϭX and CϭX compounds to be specified.…”
Section: Photoelectron Spectrometry ؊ Theoretical Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…[24,35,40] The calculated energies of the two first ionic states, associated with the ejection of an electron from the heteroatom lone pair and from the π SiϭX bond, reflect the experimentally observed ionizations fairly well for all the heterosilenes investigated. This experimental and theoretical data set enables the differences in electronic structure between related SiϭX and CϭX compounds to be specified.…”
Section: Photoelectron Spectrometry ؊ Theoretical Resultssupporting
confidence: 59%
“…The stable dimer of 31, cyclodiphosphadisiletane 33, was also found to be present, as well as, in the FVT of 30, the P-unsubstituted cyclodiphosphadisiletane 34, obtained through the intermediacy of phosphasilene 35 by elimination of isobutene and dimerization. [35] Scheme 6…”
Section: Silanimines (R 2 Si‫؍‬nrј)mentioning
confidence: 99%
“…Compounds containing a tert-butyl group attached to a nitrogen atom are known to undergo homolytic C À N bond cleavage under flash vacuum thermolysis (FVT) conditions, which results in the formation of isobutene by H elimination. [26] In this context, our aim was to access parent BN isosteres, which can be further functionalized at both the nitrogen and boron positions. [5,27] It is noteworthy in this regard that attempts to remove a tBu À N group from an azaborinine by Liu et al were unsuccessful, and thus the TBS (tert-butyldimethylsilyl) group was used as a viable Nprotecting group in 1,2-dihydro-1,2-azaborinine chemistry.…”
Section: Methodsmentioning
confidence: 99%
“…Our solution is a combination of flash vacuum thermolysis (FVT) and ultraviolet photoelectron spectroscopy (PES) . We have shown that this is the most effective method to characterize several reactive silanimines 4a,b and silylidenephosphanes in the gas phase. We have now undertaken the identification of simple silanethiones, analogues of thiformaldehyde molecule, which are rare species owing to their kinetic instability.…”
mentioning
confidence: 99%